WalnutDSA™: a group theoretic digital signature algorithm. Issue 4 (2nd October 2021) - Anshel, Iris; Atkins, Derek; Goldfeld, Dorian; Gunnells, Paul E.
ABSTRACT: This paper presents an in depth discussion of WalnutDSA, a quantum resistant public-key digital signature method based on the one-way function E-multiplication. A key feature of WalnutDSA is that it provides very efficient means of validating digital signatures which is essential for low-powered and constrained devices. This paper presents an in-depth discussion of the construction of the digital signature algorithm, and delves deeply into the underlying mathematics that facilitates analysing the security of the scheme. When implemented using parameters that defeat all known attacks, WalnutDSA is among the fastest quantum resistant signature verification methods; it performs orders of magnitude faster than ECC, even on low-end embedded hardware. WalnutDSA delivers a 12–25× speed improvement over ECDSA on most platforms, and a 31× speed improvement on a 16-bit microcontroller, making it an ideal solution for low-resource processors found in the Internet of Things (IoT).